Coevolution of female and male genital components to avoid genital size mismatches in sexually dimorphic spiders. Issue 1 (December 2016) - Lupše, Nik; Cheng, Ren-Chung; Kuntner, Matjaž
Abstract Background In most animal groups, it is unclear how body size variation relates to genital size differences between the sexes. While most morphological features tend to scale with total somatic size, this does not necessarily hold for genitalia because divergent evolution in somatic size between the sexes would cause genital size mismatches. Theory predicts that the interplay of female-biased sexual size dimorphism (SSD) and sexual genital size dimorphism (SGD) should adhere to the 'positive genital divergence', the 'constant genital divergence', or the 'negative genital divergence' model, but these models remain largely untested. We test their validity in the spider family Nephilidae known for the highest degrees of SSD among terrestrial animals. Results Through comparative analyses of sex-specific somatic and genital sizes, we first demonstrate that 99 of the 351 pairs of traits are phylogenetically correlated. Through factor analyses we then group these traits for MCMCglmm analyses that test broader correlation patterns, and these reveal significant correlations in 10 out of the 36 pairwise comparisons. Both types of analyses agree that female somatic and internal genital sizes evolve independently. While sizes of non-intromittent male genital parts coevolve with male body size, the size of the intromittent male genital parts is independent of the male somatic size. Instead, male intromittent genital size coevolves with female (external and, in part, internal) genital size. All analyses also agree that SGD and SSD evolve independently. Conclusions Internal dimensions of female genitalia evolve independently of female body size in nephilid spiders, and similarly, male intromittent genital size evolves independently of the male body size. The size of the male intromittent organ (the embolus) and the sizes of female internal and external genital components thus seem to respond to selection against genital size mismatches. In accord with these interpretations, we reject the validity of the existing theoretical models of genital and somatic size dimorphism in spiders.